On the asymmetry between subject and object relative clauses in discourse context - Renê Forster; Letícia Maria Sicuro Corrêa (Revista de Estudos da Linguagem, 2017)
This paper investigates the possibility of an effect of contextual information during the processing of sentences containing subject relative clauses (SRCs) and object relative clauses (ORCs) in Brazilian Portuguese. The predictions from one-stage models and from syntaxoriented approaches to sentence processing are outlined. An eye-tracking experiment is reported in which SRCs and ORC were presented when preceded by narrative contexts that could either favor a subject or an object relative clause analysis. The results suggest that ORCs are harder to process when compared to SRCs, no matter what discourse contexts they are inserted in. The contextual effect obtained here can be ascribed to a pre-syntactic priming, ie. a priming effect which arises during lexical access. The possibility of pre- and post-syntactic contextual effects in the processing of RCs is discussed.